141k views
11 votes
Solve the equation

5x-(2x-13)=40

User John T
by
5.5k points

2 Answers

7 votes

Answer: 9

Step-by-step explanation:

5x-(2x-13)=40

Open bracket by -1

5x-2x+13. = 40

3x. = 40-13

3x. =. 27

Divide both sides by 3

x. = 27/3.

x. = 9

PLEASE IF YOU HAVE ANY MORE QUESTIONS PLEASE COMMENT BELOW.

User Yusuf Tezel
by
5.2k points
3 votes

Answer:

9

Explanation:

open the bracket, you will have

5x-2x+13=40

collect like terms

5x-2x=40-13

3x=27

divide both side by 3

3x/3=27/3

x=9

User NewbNox
by
5.6k points